PENGARUH PENGETAHUAN PAJAK, PERSEPSI TENTANG KONSULTAN PAJAK DAN ACCOUNT REPRESENTATIVE TERHADAP MINAT MENGGUNAKAN JASA KONSULTAN PAJAK - Hadi Kusuma (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
This research aims to analyse the factor that affect the corporate taxpayers use tax consultant services. The independent variables in this research are knowledge of taxation, perception about tax consultant, and perception about account representative, and the dependent variable is interest in using the services of a tax consultant. This research is quantitative research. The population in this research is the corporate taxpayers who is registered in the KPP Kota Palembang on 2016 by taking sample of 100 respondents. The sampling technique is using Convenience Sampling. Respondents’s answer in the questionnaire were analyze using multiple linear regression analysis using SPSS Program Version 17. From the result of multiple linear regression analysis, the conclution was the perception of tax consultant From the result of multiple linear regression analysis, the conclution was the knowledge of taxation, perception about tax consultant, and perception about account representative has a positive and significant effect on corporate taxpayer’s interest of using tax consultant service in the KPP Kota Palembang.